2012
DOI: 10.1038/aps.2012.155
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride attenuates lipopolysaccharide-accelerated atherosclerosis via inhibition of NHE1-dependent endothelial cell apoptosis

Abstract: Aim: To investigate the effects of the potassium-sparing diuretic amiloride on endothelial cell apoptosis during lipopolysaccharide (LPS)-accelerated atherosclerosis. Methods: Human umbilical vein endothelial cells (HUVECs) were exposed to LPS (100 ng/mL) in the presence of drugs tested. The activity of Na + /H + exchanger 1 (NHE1) and calpain, intracellular free Ca 2+ level ([Ca 2+ ] i ), as well as the expression of apoptosis-related proteins in the cells were measured. For in vivo study, ApoE-deficient (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…It must be pointed out that LPS injection is known to aggravate atherosclerosis. However, in in vivo studies, the route of LPS injection is limited to intravenous or intraperitoneal, and the doses of LPS usually range between 0.5 mg/kg and 2.5 mg/kg BW, which is sufficient to cause atherosclerosis in apoE-deficient mice [ 49 51 ]. On the other hand, oral administration of LPSp at a high dose (300 mg/kg BW, 4 weeks) caused no significant hepatotoxicity or nephrotoxicity in rat [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It must be pointed out that LPS injection is known to aggravate atherosclerosis. However, in in vivo studies, the route of LPS injection is limited to intravenous or intraperitoneal, and the doses of LPS usually range between 0.5 mg/kg and 2.5 mg/kg BW, which is sufficient to cause atherosclerosis in apoE-deficient mice [ 49 51 ]. On the other hand, oral administration of LPSp at a high dose (300 mg/kg BW, 4 weeks) caused no significant hepatotoxicity or nephrotoxicity in rat [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevations in [Na + ] c and [Ca 2+ ] c are coupled to reduced mitochondrial [Ca 2+ ] ([Ca 2+ ] m ) in cardiomyocytes, which will decrease the energetic and redox function of mitochondria ( Murphy and Eisner, 2009 ; Bay et al, 2013 ). Elevated [Ca 2+ ] c is perceived in hyperglycemia- and LPS-induced endothelial dysfunction ( Wang et al, 2008 ; Cui et al, 2013 ), atrial fibrillation ( Neef et al, 2010 ) and in myocytes during IR injury ( Garcia-Dorado et al, 2012 ). Increases in [Na + ] c and [Ca 2+ ] c are caused by perturbed ion fluxes due to altered activity of ion channels and/or transporters, including the sodium-calcium exchanger (NCX), the sodium-hydrogen exchanger 1 (NHE-1), the ryanodine receptor regulating SR-calcium release and the sodium-potassium ATPase (Na + /K + ATPase), and targeting these ion regulating transporters has been proposed to improve cardiovascular function ( Baartscheer et al, 2003a ; Despa et al, 2012 ; Karmazyn, 2013 ; Luo et al, 2013 ; Sasahara et al, 2013 ).…”
Section: Pathogenesis Linking Diabetes and Heart Failurementioning
confidence: 99%
“…The Ca 2+ i concentration was measured by using a Fluo-4 NW kit (Invitrogen) according to our previous described procedure (Cui et al, 2013;Zhao et al, 2012). Briefly, the cell culture medium was aspirated after infection or treatment, washed with HEPES buffer (pH 7.4) once, and 1 ml of HEPES buffer containing fluorescent dye was added to cultured cells.…”
Section: Measurement Of Ca 2+ I Concentrationmentioning
confidence: 99%
“…Our previous studies have shown that increases of Ca 2+ i induced by lipopolysaccharide (LPS) enhances the activity of calpain in human umbilical vein endothelial cells (HUVECs) (Cui et al, 2013;Zhao et al, 2012). To address whether a similar mechanism was operative in Brucellainfected macrophages, the activity of calpain in macrophages was measured by using the fluorogenic peptide Suc-Leu-Leu-Val-Tyr-AMC as a substrate (Fig.…”
Section: Brucella Infection Regulates Calcium-dependent Activity Of Cmentioning
confidence: 99%